STUDENTS’ ABILITY IN WRITING COHERENTLY PARAGRAPH THROUGH OUTLINE AT THE SEVENTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF FKIP UKI TORAJA - Viktor Sumarlata; Handayani Meilin Parassa (FKIP Unismuh Makassar, 2021)
The purpose of this study was to find out the ability of students in writing coherently paragraph through outline at the seventh semester students of English Education Study Program of FKIP UKI Toraja. In this research, the researcher employed quantitative method. The population of this research is the seventh semester students of English Education Study Program of FKIP UKI Toraja which consists of 70 students and scattered into2 classes. Due to the large number of populations, the researcher choose 20 students, 10 each from class A and 10 from class B. Data collection was done by written test. Then analyzed data using student’s scores, mean scores and classifications. From 20 students, 2 students (10%) got good score, 10 students (50%) got fair score and 8 students (40%) got poor scores. The average value of students is 62.05 which is categorized into fair category.From the results of this research, the researcher concludes that the student’s ability in writing coherently paragraph through outline at the seventh semester students of English Education Study Program of FKIP UKI Toraja is fair. With these results, the researcher suggest that students can practice more and more to get good score.